Drug-Induced Liver Injury From Initial Dose of Infliximab. Issue 6 (1st June 2015) - Cheng, Fong-Kuei F.; Bridges, Edward E.; Betteridge, John D.
ABSTRACT: Acute hepatotoxicity secondary to infliximab can occur with or without autoimmunity. A growing body of infliximab drug-induced liver injury cases without autoantibody formation is emerging. Nearly all other reported cases occur after at least three doses. This suggests infliximab may have a direct cytotoxic effect on the liver. We report a case of drug-induced liver injury resulting after an initial dose of infliximab.